Mental illness in elite weightlifters <subtitle>A systematic review</subtitle> - Alice Pitt; Thomas McCabe; Jeffrey Lambert; Rachel Arnold (Hogrefe AG, 2022)
Abstract. Introduction: The mental health of elite athletes is a growing area of research however there remains a paucity of data to support evidence-based screening and prevention programmes as well as holistic yet targeted care. Olympic Weightlifting has long been associated in the media with the use of banned substances at an elite level however little is known about the mental health impact that this might represent and what the wider mental health needs of this group might be. Methods: A systematic search of PsychINFO, MEDLINE, EMCARE, EMBASE and CINAHL databases was conducted from inception up until January 2022. Peer reviewed studies of any methodology looking at mental illness or symptoms amongst current elite level Olympic weightlifters were eligible for inclusion. Results: Four articles met all inclusion criteria. Two cross-sectional studies looked at depression and anxiety and two case studies reported psychosis following long-term use of Mephentermine. Results seemed to broadly align with research looking at elite athletes in other sports however it was not possible to compare results between the two cross-sectional studies due to methodological differences. Conclusion: There is very little published research in this area and it is of varying methodological quality. A narrow subset of mental health symptoms were investigated and most of the data were based on self-reported symptoms rather than diagnostic data. Further research is needed to explore the mental health burden in this group and to inform appropriate support programmes.